Assessment of personality disorder, psychopathy and associated offending behaviour - Coid, Jeremy (Seminars in forensic psychiatry, 2024)
The assessment of personality disorder (PD) and of associated violent and other criminal behaviour are among the most complex tasks for a forensic psychiatrist. Assessment is complicated by high levels of comorbidity with clinical mental disorders, the high heterogeneity of violent and criminal behaviour, and differing and sometimes conflicting views on how PD should be conceptualised and diagnosed. It therefore requires a high level of diagnostic competence and ability to think flexibly regarding different models of mental disorder and diagnostic approaches.